Heat management of a cooling system based on the heat pipe for LED lighting fixtures - Rassamakin, A. B.; Bykov, E. V.; Khairnasov, S. M.; Rassamakin, B. M. (Technology and design in electronic equipment, 2013)
The authors have investigated a LED lamp cooling system that operates on a heat pipe basis. The paper describes the experimental stand, methods and results of the tests carried out for the different positions of the lamp at energy consumption of 196 W. It is shown that the considered cooling system ensures proper temperature of LEDs.